2005
DOI: 10.1021/jp045216s
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Studies of Structure and Bonding in Parent and Reduced Forms of the Azo Dye Orange II

Abstract: The structure and bonding of the azo dye Orange II (Acid Orange 7) in parent and reduced forms have been studied using NMR, infrared, Raman, UV-visible, and electron paramagnetic resonance (EPR) spectroscopy, allied with density functional theory (DFT) calculations on three hydrazone models (no sulfonate, anionic sulfonate, and protonated sulfonate) and one azo model (protonated sulfonate). The calculated structures of the three hydrazone models are similar to each other and that of the model without a sulfona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
83
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 78 publications
7
83
0
Order By: Relevance
“…[69][70][71] Several groups have studied dye molecules with TD-DFT [72][73][74][75][76][77] and extensive benchmark studies have been performed by Jacquemin et al [66,[78][79][80][81][82][83][84] They have shown that more conventional hybrid functionals, such as B3LYP, perform quite well in general, but long-range corrected functionals provide a beneficial effect for dyes exhibiting CT character. A diagnostic tool has been developed by Peach et al to determine the magnitude of the CT and thus the likeliness of artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…[69][70][71] Several groups have studied dye molecules with TD-DFT [72][73][74][75][76][77] and extensive benchmark studies have been performed by Jacquemin et al [66,[78][79][80][81][82][83][84] They have shown that more conventional hybrid functionals, such as B3LYP, perform quite well in general, but long-range corrected functionals provide a beneficial effect for dyes exhibiting CT character. A diagnostic tool has been developed by Peach et al to determine the magnitude of the CT and thus the likeliness of artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that it exists under azoenol (AZO) and ketohydrazone (HYZ) forms ( Fig. 1) (15)(16)(17)(18)(19)(20). In a water solution, for example, the H-atom within the O-H .…”
mentioning
confidence: 99%
“…. N intramolecular H-bond is shifted to the nitrogen site, making HYZ structure the most stable one (Ϸ95%) (20). In DMSO, the HYZ population decreases to 70%, and in solid state it becomes the only populated structure (20).…”
mentioning
confidence: 99%
See 2 more Smart Citations